Predicting farmer demand for transgenic cooking bananas in Uganda - Edmeades, Svetlana; Smale, Melinda (International Food Policy Research Institute, 2006)
In contrast to cross-breeding, genetic transformation allows for enhancement of one trait in a variety while retaining other desirable traits or attributes. Host varieties can be hybrids bred by scientists or endemic types maintained by farmers. Varieties that are popular among farmers are those whose traits or attributes are appreciated by farmers. Inserting a gene into a host variety that is already popular among farmers will increase the transgenic variety’s chances of being successful.